Les mots étrangers, les mots de l’étranger - Jean-Jacques Lecercle (Revue LISA)
The essay assesses the linguistic situation of the exile, a potentially comic figure, with intimations of tragedy (the exclusion of the foreign speaker as linguistic pharmakos), but also of liberation (the standard language is most alive when minorised by foreign words). The argument goes through a reading of Adorno’s account of his return to Germany for linguistic reasons, of Nabokov’s Pnin, of the philosophy of precarious life in the work of Guillaume Le Blanc, of Althusser’s theory of ideology and notably the concepts of interpellation and counter-interpellation.